2005
DOI: 10.1111/j.0014-3820.2005.tb00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreeding Depression, but No Inbreeding Depression in Haplodiploid Ambrosia Beetles With Regular Sibling Mating

Abstract: In sexual reproduction the genetic similarity or dissimilarity between mates strongly affects offspring fitness. When mating partners are too closely related, increased homozygosity generally causes inbreeding depression, whereas crossing between too distantly related individuals may disrupt local adaptations or coadaptations within the genome and result in outbreeding depression. The optimal degree of inbreeding or outbreeding depends on population structure. A long history of inbreeding is expected to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 55 publications
3
109
1
Order By: Relevance
“…I may have detected optimal outcrossing distance in the form of greater fitness of intrahabitat progeny had I sampled more geographically separated populations. Other studies have detected optimal outcrossing distances (Edmands 2002; but see Peer and Taborsky 2005;Heiser and Shaw 2006), though not always at spatial scales greater than the 17-162-km scale of this study. For example, Fenster and Galloway (2000) did not detect optimal outcrossing at distances greater than 2000 km.…”
Section: Discussioncontrasting
confidence: 44%
“…I may have detected optimal outcrossing distance in the form of greater fitness of intrahabitat progeny had I sampled more geographically separated populations. Other studies have detected optimal outcrossing distances (Edmands 2002; but see Peer and Taborsky 2005;Heiser and Shaw 2006), though not always at spatial scales greater than the 17-162-km scale of this study. For example, Fenster and Galloway (2000) did not detect optimal outcrossing at distances greater than 2000 km.…”
Section: Discussioncontrasting
confidence: 44%
“…However, the exact magnitude of the reduction in fitness caused by inbreeding is not known in most cases, particularly in vertebrates. On the other hand, too much outbreeding can also have negative fitness consequences (Pusey and Wolf, 1996;Peer and Taborsky, 2005;Kokko and Ots 2006). So our results showing an absence of inbreeding depression, which may have several explanations, should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 72%
“…Some studies have demonstrated the existence of inbreeding depression in life-history (Slate et al, 2000;Liberg et al, 2005;Ralls et al, 1979) and morphological traits (Fredrickson and Hedrick 2002;GĂłmez et al 2009), while others have not Hedrick and Kalinowski, 2000; Peer and Taborsky, 2005). Thus, inbreeding depression is a complex phenomenon that defies easy prediction.…”
Section: Discussionmentioning
confidence: 99%
“…However, outbreeding depression will be more important in the second generation (F2) after a BP cross due to the breakdown of co-adapted genes complexes in parental lineages after recombination events (Edmands 1999(Edmands , 2007. Outbreeding depression has been mainly described in plants and invertebrates (Waser and Price 1994;Burke and Arnold 2001;Peer and Taborsky 2005;Escobar et al 2008) but more rarely in vertebrates (Marr et al 2002;Edmands 2007;McClelland and Naish 2007;Granier et al 2011;Huff et al 2011). Few studies on outbreeding depression have been carried through to the second (Palmer and Edmands 2000;Smoker et al 2004;Dann et al 2010;Houde et al 2011;Huff et al 2011;Willett 2012) or third generation (Edmands 1999, Fenster andGalloway 2000).…”
Section: Introductionmentioning
confidence: 99%